Розроблення оптимізованої моделі логістичних ланцюгів постачання-розподілу підприємств - Сергієнко, Олена Андріанівна; Голофаєва, І. П.; Швець, А. Д. (Видавничий дім "Гельветика", 2019)
У статті запропоновано модель логістичної системи в напрямі вдосконалення бізнес-процесів управління виробництвом і забезпечення його ефективності на прикладі ПАТ "Харківська бісквітна фабрика", побудована на основі головних принципів логістичного підходу, що вимагають інтеграції матеріального та технічного забезпечення, транспорту, виробництва, збуту і передачі інформації про товари та сировинні бази в єдину систему задля підвищення ефективності роботи у кожній із цих сфер і загальної ефективності. Роботу присвячено розробленню комплексу моделей підвищення ефективності логістичної діяльності підприємств. Запропонована методика моделювання ланцюгів постачань-розподілу на основі імітаційного моделювання є достатньо гнучкою і легко адаптується у межах SCOR-моделі для якісніших і швидших змін у вдосконаленні процесів та підвищенні їх ефективності. З метою удосконалення діяльності та підвищення рівня ефективності функціонування досліджуваного підприємства ПАТ "Харківська бісквітна фабрика" авторами змодельовано сценарії логістичних ланцюгів постачань-розподілу оптимізованої структури. Побудована модель дає змогу імітувати різні сценарії з організації управління ланцюгами постачань та здійснювати контроль над динамікою бізнес-процесів шляхом регулювання, координування та оптимізації існуючої логістичної системи.

The business process optimization theory is the base for efficient logistics management system developing as a well-managed process of information and product flows between suppliers, enterprises and consumers through the integration of material and technical support, transport, production, marketing and transfer of information, goods and raw materials into an unified system in order to improving efficiency in each of these areas and, as a result, overall cross-industry efficiency. The work is devoted to the development of complex models of improving the efficiency of enterprises’ logistic system and method of modeling supply-distribution chains based on simulation modeling within SCOR models for qualitative and rapid changes in improvement process and increase of their efficiency was proposed. The article deals with a step-by-step algorithm for developing an enterprise optimized model of logistics supply chains in the direction of improving production management business processes and ensuring its efficiency on the example of the company PJSC "Kharkiv biscuit factory". The proposed model includes three main steps: 1 - Construction of the enterprise supply chains structure; 2 - Structuring of logistic production processes and their modeling; 3 - Scenarios development for logistics supply chain distribution optimizationand. The proposed model allows to solve the following set of issues: Choosing the structure type and its network; Establishing relationships by the levels (coordination, organization); Supply chain management (monitoring, control); Formation the set of optimization methods; Selection and application of simulation modeling tools; Reproduction of the real system; Development of management organization scenarios (coordination, control); Conducting experiments and simulations; Forcasting estimates of operating logistics supply and distribution systems.The built model allows to simulate different scenarios for the supply chain management organization and to monitor the business processes dynamics by regulating, coordinating and optimizing the existing logistics system.
Development of optimized model of enterprises' supply-distribution logistics chains
Keywords: економічна діяльність; бізнес-процеси; управління; логістика; оптимізація; підприємницька діяльність; supply chain; supply chain management; logistics; logistics system; optimization; imitation models